THE PERCEPTION OF TARGET PRINTING IN THE BANKING SECTOR: AN APPLICATION ON THE BANKS OPERATING IN VAN - OĞRAK, Abdullah; ATAMAN, Sıddık; ATAMAN, Fikriye (IKSAD JOURNAL, 2022)
One of the criteria to measure success in the performance evaluation process of the personnel working in the institutions is to set a target. While the target is expressed as the desired final result or the realization of the desired thought, the sales target is expressed as the sales amount determined by the senior management of the personnel working as a salesperson in a commercial enterprise within a certain period. All kinds of psychological stress and difficulties experienced by the personnel to achieve and achieve the sales target are defined as Target pressure. The sector with the highest target pressure among all sectors is the banking sector with 17.4%. In this study, it is aimed to determine whether the perception of target pressure in the banking sector varies according to the demographic characteristics of the bank employees. For this purpose, this research has been conducted for approximately 320 bank personnel working in 35 bank branches, 3 of which are public and 9 are private banks. Target Pressure scale developed by Soygür and Aydın was used to reach the sample group determined within the scope of the research. The data obtained by the survey method were analyzed with SPSS 20 program and frequency analysis, T-test and ANOVA test were applied. As a result of the analyzes, while there was a significant difference between the service/task position of the participants and perception of target pressure, there was no significant difference between age, gender, marital status, duration of service and target pressure.